2011
DOI: 10.1159/000323374
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Subthalamic Nucleus Stimulation in the Treatment of Neurodegeneration with Brain Iron Accumulation Type 1

et al.

Abstract: Background: Neurodegeneration with brain iron accumulation type 1 (NBIA1), previously called Hallervorden-Spatz disease, is a rare neurodegenerative condition with abnormal brain iron accumulation. There have been some reports of deep brain stimulation (DBS) in the treatment of NBIA1. However, the target was usually the globus pallidus internus or thalamus. Objectives/Methods: We present a case of NBIA1 in a 16-year-old male who was treated with bilateral subthalamic nucleus (STN)-DBS and explored its efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A brief review of more recent literature on NBIAs reveals that, in large series of patients that were published mostly after the identification of causative genes, although generalized, truncal and neck dystonia are described, and a more specific phenotypic description of the dystonia is largely missing . For example, 87% of 52 patients with panthothenate kinase 2 ( PANK2 ) mutations had dystonia, including action‐induced axial dystonia, but it is unknown how many patients had extensor axial dystonia; in the largest series of deep brain stimulation in 23 patients with NBIAs, the dystonia characteristics were not provided …”
Section: How Common Is Dystonic Opisthotonus In Nbias?mentioning
confidence: 99%
“…A brief review of more recent literature on NBIAs reveals that, in large series of patients that were published mostly after the identification of causative genes, although generalized, truncal and neck dystonia are described, and a more specific phenotypic description of the dystonia is largely missing . For example, 87% of 52 patients with panthothenate kinase 2 ( PANK2 ) mutations had dystonia, including action‐induced axial dystonia, but it is unknown how many patients had extensor axial dystonia; in the largest series of deep brain stimulation in 23 patients with NBIAs, the dystonia characteristics were not provided …”
Section: How Common Is Dystonic Opisthotonus In Nbias?mentioning
confidence: 99%
“…There is no treatment for this disease, although a few preliminary studies suggest the safety and tolerability of deferiprone as a chelating agent for both intra- and extra-neuronal iron accumulation[1415] and also that of bilateral sub-thalamic nucleus deep brain stimulation;[16] the only option that remains is symptomatic treatment of psychiatric and neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral STN DBS improved primary cervical dystonia with an efficacy comparable to that of GPi DBS (Ostrem et al, 2011). Improvements in secondary dystonia such as neurodegeneration with brain iron accumulation (NBIA) also have been reported (Ge et al, 2011;Zhang et al, 2006). Moreover, it has been claimed that STN is a better target than GPi for segmental dystonia because stimulation-related adverse effects such as bradykinesia, which has been repeatedly reported in GPi DBS, does not occur with STN DBS (Ostrem et al, 2011).…”
Section: Target Selectionmentioning
confidence: 95%
“…There are reports of favorable (65-91%) responses (Castelnau et al, 2005;Clement et al, 2007;Krause et al, 2006;Mikati et al, 2009;Umemura et al, 2004), but others reported only 20-30% improvement (Isaac et al, 2007;Shields et al, 2007). A single case report of STN DBS on a NBIA patient showed 84% improvement at 3 years after surgery (Ge et al, 2011). It is surprising that motor symptoms in NBIA can improve with DBS, given that structural abnormalities in the brain MRI usually meet the exclusion criteria for DBS in primary dystonia (Kupsch et al, 2006;Vidailhet et al, 2005).…”
Section: Nbiamentioning
confidence: 99%